Women and the Indian Freedom Movement: Exploring the Contribution of Indian Women in the 1857 Uprising (Journal of Advances and Scholarly Researches in Allied Education, 2014)
In the great uprising of 1857 some Indian women boldly contributed for the cause of freedom. Maharani Lakshmibai the bravest of all rebels shines like a bright star on the horizon of that mass movement. She was wholeheartedly assisted not only by the Hindu women but Muslim women also. The number of such women crusaders was very few. The mobility of women was by and large restricted to the four walls of their dwellings. An average Indian woman had no access to school, college and other public places. A fairly large majority of them lived as deaf and dumb driven cattle.